Daytime variation of perioperative myocardial injury in non-cardiac surgery and effect on outcome. Issue 11 (12th December 2018) - du Fay de Lavallaz, Jeanne; Puelacher, Christian; Lurati Buse, Giovanna; Bolliger, Daniel; Germanier, Dominic; Hidvegi, Reka; Walter, Joan Elias; Twerenbold, Raphael; Strebel, Ivo; Badertscher, Patrick; Sazgary, Lorraine; Lampart, Andreas; et al.
Abstract : Objective: Recently, daytime variation in perioperative myocardial injury (PMI) has been observed in patients undergoing cardiac surgery. We aim at investigating whether daytime variation also occurs in patients undergoing non-cardiac surgery. Methods: In a prospective diagnostic study, we evaluated the presence of daytime variation in PMI in patients at increased cardiovascular risk undergoing non-cardiac surgery, as well as its possible impact on the incidence of acute myocardial infarction (AMI), and death during 1-year follow-up in a propensity score–matched cohort. PMI was defined as an absolute increase in high-sensitivity cardiac troponin T (hs-cTnT) concentration of ≥14 ng/L from preoperative to postoperative measurements. Results: Of 1641 patients, propensity score matching defined 630 with similar baseline characteristics, half undergoing non-cardiac surgery in the morning (starting from 8:00 to 11:00) and half in the afternoon (starting from 14:00 to 17:00). There was no difference in PMI incidence between both groups (morning: 50, 15.8% (95% CI 12.3 to 20.3); afternoon: 52, 16.4% (95% CI 12.7 to 20.9), p=0.94), nor if analysing hs-cTnT release as a quantitative variable (median morning group: 3 ng/L (95% CI 1 to 7 ng/L); median afternoon group: 2 ng/L (95% CI 0 to 7 ng/L; p=0.16). During 1-year follow-up, the incidence of AMI was 1.2% (95% CI 0.4% to 3.2%) among morning surgeries versus 4.1% (95% CI 2.3% to 6.9%) among the afternoon surgeries (corrected HR for afternoon surgery 3.44, bootstrapped 95% CI 1.33 to 10.49, p log-rank=0.03), whereas no difference in mortality emerged (p=0.70). Conclusions: Although there is no daytime variation in PMI in patients undergoing non-cardiac surgery, the incidence of AMI during follow-up is increased in afternoon surgeries and requires further study. Clinical trial registration: NCT02573532 ;Results.